The Printer's Devil and English Language Infractions in the Ghanaian Print Media (Journal of Science and Technology, 2016)
Our study is on English Language infractions, particularly, grammatical absurdities, unacceptably blamed on an ogre named the Printer's Devil by journalists. It is a sequel to an earlier article, AN ANALYTICAL COMMENTARY ON SOME TELLING GRAMMATICAL ERRORS ON SOME FREQUENCY MODULATION STATIONS IN KUMASI, GHANA. The paper forms part of an ongoing research into “Street Language and its effect on Educated Ghanaian English”. Here, we present the way some of our journalists sloppily handle the English Language, subjugating good language and grammar to message while dangerously appearing oblivious of the effect of what they write on readers, especially students in tertiary institutions who may be good readers, and who often have to depend on newspapers as sources of information in their research activities. Although our aim in this research endeavour is to see by how much the English Language in Ghana is being nativised,we suggest that journalese or technicalese cannot mean deliberate or careless jettisoning of grammatical norms. The archetypal Printer's Devil should not be made to bear the brunt of the journalist's grammatical inadequacies.